Non-Alcoholic Fatty Liver Disease (NAFLD) Is an Independent Risk Factor for Developing New-Onset Diabetes After Acute Pancreatitis: A Multicenter Retrospective Cohort Study in Chinese Population - Lv, Yingqi; Zhang, Jun; Yang, Ting; Sun, Jinfang; Hou, Jiaying; Chen, Zhiwei; Yu, Xuehua; Yuan, Xuelu; Lu, Xuejia; Xie, Ting; Yu, Ting; Su, Xianghui; et al. (Frontiers in Endocrinology, 2022)
Background: Numerous studies validated frequent glucose dysfunction in patients with acute pancreatitis (AP). However, the prevalence of new-onset diabetes in individuals after a first episode of AP varies widely among previous studies. This study aims to determine the incidence of post-acute pancreatitis diabetes mellitus (PPDM-A) in Chinese people and further identify potential risk factors that influence diabetes development in patients with AP. Methods: This was a multi-center retrospective cohort study including 6009 inpatients with a first attack of AP. A total of 1804 patients with AP without known endocrine pancreatic disorders or other pancreatic exocrine diseases were eligible for analysis. Data was collected from medical records by hospital information system and telephone follow-ups after discharge. The multiple logistic regression analysis was established to evaluate the potential influencing factors of PPDM-A. Results: The prevalence of newly diagnosed diabetes after a first episode of AP in China was 6.2%. Data showed that patients who developed PPDM-A were more likely to be younger (X2= 6.329, P = 0.012), experienced longer hospital stays (X2= 6.949, P = 0.008) and had a higher frequency of overweight or obesity (X2= 11.559, P = 0.003) compared to those with normal glycemia. The frequency of stress hyperglycemia on admission (X2=53.815, P < 0.001), hyperlipidemia (X2= 33.594, P < 0.001) and non-alcoholic fatty liver disease (NAFLD) (X2=36.335, P < 0.001) were significantly higher among individuals with PPDM-A compared with control group. Also, patients with PPDM-A were more likely to be hyperlipidemic AP (X2=16.304, P = 0.001) and show a higher degree of severity (X2=7.834, P = 0.020) and recurrence rate (X2= 26.908, P < 0.001) of AP compared to those without diabetes. In addition, multiple logistic regression analysis indicated that stress hyperglycemia, hyperlipidemia, NAFLD and repeated attacks of AP were the independent influence factors for developing PPDM-A. Conclusion: Our study first demonstrated the prevalence of secondary diabetes in Chinese patients after AP. The disorder of glucose metabolism in individuals with AP should be regularly evaluated in clinical practice. Further studies are needed to verify the relationship between liver and pancreas in keeping glucose homeostasis under AP condition.